2018
DOI: 10.1016/j.celrep.2018.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Gsk3b Reduces Nfkb1 Signaling and Rescues Synaptic Activity to Improve the Rett Syndrome Phenotype in Mecp2-Knockout Mice

Abstract: Rett syndrome (RTT) is the second leading cause of mental impairment in girls and is currently untreatable. RTT is caused, in more than 95% of cases, by loss-of-function mutations in the methyl CpG-binding protein 2 gene (MeCP2). We propose here a molecular target involved in RTT: the glycogen synthase kinase-3b (Gsk3b) pathway. Gsk3b activity is deregulated in Mecp2-knockout (KO) mice models, and SB216763, a specific inhibitor, is able to alleviate the clinical symptoms with consequences at the molecular and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 70 publications
(76 reference statements)
2
36
1
Order By: Relevance
“…A study by Kishi and colleagues [52] on the cortex of Mecp2 -null mice demonstrated an abnormal upregulation of NF-κB signaling, which reduction ameliorated the dendritic complexity of callosal projection neurons and prolonged their normal lifespan. Similarly, a marked decrease in inflammation markers was observed in the cerebellar area of Mecp2 -knockout mice after treatment with a specific glycogen synthase kinase-3b (Gsk3b) inhibitor that attenuated the nuclear NF-κB activity [53]. Together, these evidence and our results suggest the hypothesis that NF-κB pathway dysregulation could play a significant role in RTT pathophysiology, as already proven in rheumatoid arthritis, inflammatory bowel disease, multiple sclerosis, atherosclerosis, systemic lupus erythematosus, type I diabetes, chronic obstructive pulmonary disease and asthma [54].…”
Section: Discussionmentioning
confidence: 99%
“…A study by Kishi and colleagues [52] on the cortex of Mecp2 -null mice demonstrated an abnormal upregulation of NF-κB signaling, which reduction ameliorated the dendritic complexity of callosal projection neurons and prolonged their normal lifespan. Similarly, a marked decrease in inflammation markers was observed in the cerebellar area of Mecp2 -knockout mice after treatment with a specific glycogen synthase kinase-3b (Gsk3b) inhibitor that attenuated the nuclear NF-κB activity [53]. Together, these evidence and our results suggest the hypothesis that NF-κB pathway dysregulation could play a significant role in RTT pathophysiology, as already proven in rheumatoid arthritis, inflammatory bowel disease, multiple sclerosis, atherosclerosis, systemic lupus erythematosus, type I diabetes, chronic obstructive pulmonary disease and asthma [54].…”
Section: Discussionmentioning
confidence: 99%
“…Then, the sections were microwaved in 10 mM citrate buffer (pH 6.0) at 95°C for 20 min to perform antigen retrieval. After being blocked with goat serum for 30 min, the sections were incubated with the primary antibody (anti-Styk1 ab97451, 20 anti-AKT1 (phospho S473) ab81283, 21 anti-pan-AKT (phospho T308) ab38449, 22 anti-GSK3 beta (phospho Y216) ab75745, 23 anti-GSK3 beta (phospho S9) ab75814, 24 anti-E Cadherin ab40772 25,26 from Abcam, Cambridge, UK; and N-cadherin (D4R1H) 27 from Cell Signaling Technology, Danvers, MA, USA) at 4°C overnight. After being washed in PBS (phosphate-buffered saline), the sections were incubated with the appropriate horseradish peroxidase (HRP)-labeled goat anti-rabbit/mouse antibodies.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…For instance, the guanyl-nucleotide exchange factor activity GO term (GO:0005085; Figure 5C, far-left) includes guanine nucleotide exchange factors (GEFs) which activate Rho-family GTPases to regulate a diverse suite of cellular functions, including cell-cycle progression, the actin cytoskeleton, and transcription [72]. Additionally, genes involved in peptidyl-serine phosphorylation (GO:0018105; Figure 5C, mid-left), represent a broad class of kinases, including those involved in neurological disease and inflammation [63, 73]. Finally genes involved in transcriptional repressor activity (GO:0001078, Figure 5C, mid-right), include proteins involved in regulating hematopoiesis and controlling neurological development [7476].…”
Section: Resultsmentioning
confidence: 99%